Strength and durability of lime-treated jarosite waste exposed to freeze and thaw - Gupta C.; Prasad A. (My University, 2025)
An alternate freezing and thawing cycle (F-T) is a weathering process that is very common in cold regions. In a laboratory, the durability of any stabilized or nonstabilized material can be studied by subjecting the material to alternate cycles of freezing and thawing. In this study, a study of strength and durability of lime-treated jarosite waste exposed to freezing and thawing is investigated. Jarosite with different ratios of lime is compacted in the laboratory and exposed to a maximum of five freezing and thawing cycles. In addition, an attempt has been made to quantify the potential of lime, F-T cycle, and ratio of F-T cycle (C)/curing period (t), in the assessment of unconfined compressive strength (qu) and split tensile strength (qt) of lime-treated jarosite. A number of unconfined compressive and splitting tensile strength tests are carried out on jarosite samples stabilized with various lime contents. The results show that both qu and qt increase polynomially with the increase in lime content (L), and a power function has been fitted to assess the optimum relationship between qu and C/t ratio, as well as between qt and C/t ratio. It is observed that for the relationship among qu, L, and C/t, as well as qt, L, and C/t, the optimum fit could be obtained after applying a power equal to 1.3 to the lime content (L) parameter and -0.25 to the C/t ratio parameter. Finally, a unique relationship between qt and qu is also established, i.e., qt = qu = 0.17, being independent of the parameters C/t ratio and lime content (L). © 2017 American Society of Civil Engineers.